Who stands to benefit? Wellbeing, belonging and challenges to equity in engagement in extra-curricular activities at university. (July 2022) - Winstone, Naomi; Balloo, Kieran; Gravett, Karen; Jacobs, Daniel; Keen, Harry
Students' engagement in extra-curricular activities can play a significant role in their development of a student identity, as well as leading to a greater sense of belonging and wellbeing. However, individual characteristics such as sociability may influence the likelihood of students engaging in extra-curricular activities. We collected mixed mode data from two online surveys to explore students' perceptions of the impact of engagement in extra-curricular activities on their experience at university, as well as the mediating role of engagement in extra-curricular activities in the relationships between extraversion and wellbeing and sense of belonging to the University. Our data demonstrate that extraversion is positively associated with both belonging and wellbeing, and that engagement in extra-curricular activities also mediates these relationships. Our qualitative data uncover further nuances in engagement with extra-curricular activities; while many perceived outcomes are positive, some students express regret at opportunities missed, and find it challenging to balance extra-curricular activities and their studies. Taken together, these findings indicate that not all students stand to benefit equally from engagement in extra-curricular activities. Providing a range of opportunities that are accessible to a wide range of students may promote equity in participation in extra-curricular activities.